Rupert Hatton's Story - Lofts, Norah, 1904-; Grahame Johnstone, Anne; Grahame Johnstone, Janet (Nashville [Tenn.] T. Nelson, 1973)
In eighteenth-century England, a boy's passion for the violin, despite his father's opposition, causes a disaster which results in a totally new life.
Published in 1972 under title: Rupert Hatton's tale.
Keywords: Violin -- Fiction